Penggambaran Prancis dalam Novel Arab Faraj: Kajian Sastra Perjalanan Carl Thompson - Utami, Shinta Fitria; Primadani, Erip (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
Travel writing or travelogue is currently a popular field of study. However, it has yet to receive a lot of attention in the Arabic literature tradition. This article aims to break down the travel story found in the Arabic Novel Faraj. The research applies a descriptive-analytical approach to analyze and present an in-depth analysis. Data collection begins with meticulous reading and translation to ensure an adequate understanding. Words, phrases, or sentences that contain travel narratives are recorded as data. These data are then analyzed using literature relevant to travel writing, as proposed by Carl Thompson, to examine patterns of depicting travel in terms of reporting the world, revealing the self, and representing the other. The results of the investigation indicate that, through the novel Faraj, the author sees France, which is considered as a superior, free, and advanced Western country, experiencing significant demonstrations to challenge authority, mirroring Egyptian events. The author uses the fictional character Nida Abdul Qadir to show how the 1968 demonstrations in France influenced her life as a student activist.